Globalization and Labour in Developing Countries: India. (April 2018) - Nathan, Dev
This article deals with labour under globalizing conditions in developing countries, particularly India. * It poses the question of how the convergence in global incomes and inequality has impacted on labour. In the context of the experience of the developing countries as a whole, the article argues that strategic interventions in global world markets can increase the share of labour in the benefits from globalization. Thereafter, the article deals with the position of India and shows that there has been an increase in rural real wages and in agricultural productivity after globalization. The article argues that globalization provides space for the upgradation of the capacities of labour in order to improve real wages and the quality of employment.